Renal failure in patients with hematological malignancies (literature review) - E. G. Gromova (Онкогематология, 2021)
Dysfunction of the natural detoxification organs remains a significant problem in patients with hematological malignancies. The reasons for the development of renal failure are associated with the individual characteristics of the malignant process, the patient’s comorbid background, the toxic effects of anticancer treatment and its complications. The efficacy of many anticancer drugs correlates with their dose, an increase in which is associated with increased toxic effects on healthy organs, including the kidneys. The main reasons for the renal failure development in hematological cancer patients and syndromes that prevent adequate antitumor therapy are considered. Diagnostic algorithm optimization and supportive intensive care of acute renal failure is the key to the successful application of highly effective modern protocols of drug anticancer treatment.A special group is represented by patients suffering from monoclonal gammopathies with acute renal injury and hyperproduction of immunoglobulins free light chains. Renal failure can be the onset and dominant clinical manifestation of multiple myeloma in 18–56 % of cases, of which 10 % require programmed hemodialysis. Antitumor therapy in presence of renal failure is limited, and in some cases impossible, while the renal function recovery is associated with an increase in survival.Organ damage in oncohematological patients can be a manifestation of paraneoplastic syndromes. Tumor lysis syndrome is an urgent problem of oncohematological practice associated with the development of acute renal injury and high mortality.The development of organ failure in oncohematological patients causes significant difficulties in antitumor therapy; a combination of organ dysfunction and the resulting change in anticancer therapy regimens worsen the prognosis. Modern methods of organ failure prevention and treatment can successfully solve complex clinical problems.